Elaboração e análise da aplicabilidade de um manual de orientação de atividade de vida diária para cuidadores e/ou familiar de pacientes pós acidente vascular encefálico - PERES, Geovana de Souza Paixão (2023)
Introduction: The present study was based on the interest of the students in the subjects that deal with the Daily Life Activity, the knowledge and experiences acquired in the extension project “Neurological Rehabilitation and Occupational Therapy: a focus on daily life of activity” added to the experiences during the mandatory stages in the Basic Health Unit and the Family Health Support Center. Objective: To analyze the effectiveness of the use of an ADL guidance manual to assist caregivers in the care of people with stroke sequelae. Methodology: This is a descriptive exploratory qualitative study, carried out in the extension project "Neurological Rehabilitation and Occupational Therapy: a focus on ADLs" with people who have suffered stroke and their respective caregivers. The data collection was performed through semi-structured interviews and was presented in three phases, and their data were analyzed through content analysis. Results: The results regarding the data collected in the interviews were presented in the form of a case study and then the guidelines manual is presented as a result of this research. Discussion: it was distributed in the discussion of the methodological design and data collection instruments, profile of the participants, contributions of the manual as an instrument of education and health and limitations of the study. Conclusion: It was concluded in the study that the use of manuals as an education and health tool for caregivers of persons suffering from stroke is an effective strategy, as it contributes as a tool to help the caregiver in face of the difficulties presented, and As a consequence in the effective improvement of the client.